The Government-Farmer Conflict in Sudan: A Deepening Crisis in Agriculture - Muhammad, Alsadig Siddig Abkar; Purba, Arief Marizki (Talenta Publisher, 2024)
This paper explores the ongoing struggles faced by Sudanese farmers within the broader context of government policies and socio-political challenges affecting the agricultural sector. Despite agriculture being the backbone of Sudan's economy, the sector has been hindered by inadequate government support, land disputes, poor infrastructure, and the exacerbating impacts of climate change. Through an analysis of recent farmer protests, land ownership issues, and the state's responses, this paper reveals a cycle of alienation and unrest among rural communities. Drawing from a range of sources, it argues that the government's failure to implement effective land reforms and provide adequate support for small-scale farmers has deepened the rural-urban divide and threatened food security. The paper concludes by calling for comprehensive reforms, including secure land tenure, increased rural investment, and climate adaptation strategies, to create a more sustainable and resilient agricultural sector.